a Vacant Residential Tax Design as a Solution for Housing Problem in Indonesia - RIRIN WAHYUNI NASRUL (JURNAL PAJAK INDONESIA, 2025)
This study explores the appropriateness of designing vacant residential tax to solve the complex housing problem in Indonesia, inefficiencies in the residential market. That condition has arisen from various factors. With a large population, population growth significantly drives housing demand. Although government initiatives promoting homeownership through subsidies have positive externalities, they have also led to these subsidies being viewed as part of a new, higher equilibrium price. Additionally, rising property values encourage higher-income individuals to invest in real estate, further increasing demand. On the other hand, the high costs of building new homes result in slow supply growth. Consequently, this imbalance makes homes increasingly unaffordable, with prices outstripping income growth. On the other hand, the elevated vacancy rate is another sign of inefficient resource allocation in the market. While there is a supply shortage, many properties remain unused. The goal in assessing this issue is to accomplish this by examining the present state of Indonesia's housing market, assessing how taxation can effectively address market failures, and ultimately reviewing the proposed tax structure for unoccupied residential properties. The study employs a qualitative research methodology, drawing on OECD guidelines, Indonesian tax law, policy documents, and academic literature to examine the pertinent tax issues. This study argues that the Vacant Residential Tax could be a viable solution for influencing behavior in residential investment decisions, easing supply constraints, and stabilizing housing prices in Indonesia. It seeks to accomplish this by examining the current state of Indonesia's housing market, assessing how taxation can effectively address market failures, and analyzing the proposed tax design for unoccupied residential properties.